PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.B MTs.HUBBULWATHAN DURI - Yuliana '; Titi Solfitri Titi Solfitri; Susda Heleni Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
bstract: This study aims to improve the learning process and learning outcomes math class VIII B Hubbulwathan MTs Duri by applying Cooperative learning model Student Teams Achievement Division (STAD) type. The subjects were students of class VIII B with heterogen academic ability. This research is a class action with two cycles. Each cycle has four steps, the steps are the planning, implementation, observation and reflection. Results showed activity sheets and teacher observation of students have not done well yet after taking action. There is no improvement in thestudents learning process and no increasing in the number of students who achieved at UH minimum completeness criteria end of each cycle compared to the number of students who achieve minimum completeness criteria on base score. The results of this study indicate that the application of cooperative learning model Student Teams Achievement Division (STAD) can not improve the process of learning and improving mathematics learning out comes of VIII B Student in the MTS Hubbulwathan Duri on second semester of academic year 2013/2014, because the students do not master the prerequisites lessons as supporting material of the subject being studied.Keywords: Mathematics Learning Outcomes, Cooperative Learning, Student Teams Achievement Division (STAD), Classroom Action Research